Pengaruh Perencanaan Pajak dan Intellectual Capital Terhadap Nilai Perusahaan (Studi Empiris Pada Perusahaan Manufaktur yang Teradaftar di Bursa Efek Indonesia Periode 2017-2020): (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2017-2020) - Mia Indriany; Herman Wijaya; Lulu Nailufaroh (Jurnal Inovasi dan Kreativitas (JIKa), 2021)
Abstract: Problems: The government wants a maximum tax payment while the company is minimum. The company carries out tax planning to minimize the tax burden in order to increase profits by involving the intellectual capital owned by the company in order to increase the firm value. Purpose: To examine the effect of tax planning and intellectual capital on firm value. Methodology: This study uses quantitative methods with secondary data types. Results/Findings: Tax planning and intellectual capital have a positive effect on firm value. Tax planning and intellectual capital can explain the firm value as much as 37,8%. Paper Type: Correlation Research. Keywords: Tax Planning, Intellectual Capital, Firm Value